2015
DOI: 10.1088/0268-1242/30/12/125006
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of apparent activation energy and lifetime estimation in NAND flash memory

Abstract: Misunderstanding apparent activation energy (E aa ) can cause serious error in lifetime predictions. In this paper, the E aa is investigated for sub 20 nm NAND flash memory. In a hightemperature (HT) regime, the interface trap (N it ) recovery mechanism has the greatest impact on the charge loss. However, the values of E aa and E a(Nit) have a wide difference. Also, the lifetime of the device cannot be estimated by the Arrhenius model due to the E aa roll-off behavior. For the first time, we reveal the origin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Furthermore, it been reported that lateral charge transport in the conduction band of the nitride layer is responsible for non-Arrhenius retention [19,20]. The thermal emission and lateral transport are faster than the tunneling charge loss and thus the data retention time is dependent on temperature [21,22]. In this experiment, the ratio for the dielectric recovery using delayed pulse, temperature, and time were calculated from the universal unified detrapping matrix equation [3].…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, it been reported that lateral charge transport in the conduction band of the nitride layer is responsible for non-Arrhenius retention [19,20]. The thermal emission and lateral transport are faster than the tunneling charge loss and thus the data retention time is dependent on temperature [21,22]. In this experiment, the ratio for the dielectric recovery using delayed pulse, temperature, and time were calculated from the universal unified detrapping matrix equation [3].…”
Section: Resultsmentioning
confidence: 98%
“…Lee et al [26] studied E aa for sub 20nm NAND flash memory. They revealed the anomalous origin feature at E aa (apparent activation energy) and derived the mathematical formula which is a function of E a (the interface trap) in NAND flash, and used the proposed mathematical equation to estimate the lifetime of the NAND flash.…”
Section: B Model-based Techniques For Optimizing Reliability Of Nand Flash Memorymentioning
confidence: 99%